The evaluation of ultrasonographic hip measurement differences among physicians according to the Graf method in newborns: Ultrasonographic measurements between physicians in the newborn - Altunkılıç , Tarık; Arı , Bünyamin; Yetiş , Mehmet; Kılıçaslan , Nihat; İnceoğlu , Feyza (Journal of Surgery and Medicine, 2022)
Background/Aim: Hip ultrasonography (USG) is the most important diagnostic method in developmental hip dysplasia in newborns. However, a disadvantage of the ultrasonography method is that there can be measurement differences among doctors measuring the same hip. We aimed to investigate the causes and solutions of this situation. We further strived to measure the hip ultrasonography performed by different physicians using the Graf method and comparing the obtained values. Methods: Hip USGs of newborns admitted to Malatya Turgut Ozal University Faculty of Medicine Hospital between Jan. 8, 2020 and Jan. 5,.2021 were measured and classified using the Graf method. The study type is consistent with retrospective cohort studies. Newborns aged 0-22 weeks without any additional pathology were included in the study. A radiologist and two orthopedists measured and interpreted the images separately in accordance with the Graf method. The first hip measurements (R1) were made by the radiologist (R) with the USG device, and they were classified according to alpha and beta angles; two printouts were made. The first orthopedic specialist (OS1) and the second orthopedic specialist (OS2) made their measurements with printouts. Subsequently, the results from the physicians were compared. Results: A statistically significant difference was found between R1-OS2 (P < 0.001) and OS1-OS2 (P < 0.001) in terms of the Graf classifications. No statistically significant difference was found between R1 and OS1 in terms of the Graf classification (P = 0.562). A statistically significant difference was found between R1-OS2 (P < 0.001) and OS1-OS2 (P = 0.048) angles (alpha and beta) measurements. While R1 and OS1 measurements were compatible with each other, OS2 measurements were found to be inconsistent. Conclusion: We think that there may be differences in angle measurements and the Graf classification among physicians who perform hip ultrasonography in newborns, and the most important way to correct this is through regular participation of physicians in subject-specific trainings.